Revitalisasi Permainan Tradisional 17 Agustus sebagai Sarana Peningkatan Motivasi Belajar Anak - Juhariyah Juhariyah; Akhmad Akmal Khoiro; Naf’an Tarihoran (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Traditional games are an important part of cultural heritage that carry educational values and can serve as an enjoyable and effective learning medium for children. Through the Community Service Program (KKN), university students organized traditional game competitions during the Independence Day celebration with village children. The activities aimed not only to provide entertainment but also to foster children’s learning motivation, enhance social interaction, and develop their personal character. This study employed observation, interviews, and documentation to collect accurate data. A total of 30 children were recorded as participants, although the actual number of participants in the competitions was higher. Ten children were purposively selected as interview respondents to gain deeper insights into their experiences. The results revealed that most children felt happy and enthusiastic while participating in the competitions. They also acquired important educational values such as teamwork, concentration, patience, perseverance, and enthusiasm for learning. Moreover, the majority of respondents stated that participating in the traditional games motivated them to be more engaged in school learning and encouraged them to study harder after the activities. Therefore, the revitalization of traditional games during the Independence Day celebration can serve as an effective alternative medium to enhance children’s learning motivation, strengthen social interaction, and preserve local cultural heritage. This study suggests that integrating cultural activities into educational practices can positively influence children’s attitudes toward learning while maintaining the community’s cultural identity.